The Influence of the PjBL Learning Model on the Biology Learning Outcomes of Class X Students at SMA Negeri 2 Tondano - Atris Diana Kabaena; Jemmy L. Sumakul ; Ferny M. Tumbel (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study seeks to examine the disparity in mean scores between students instructed through the project-based learning approach and those taught using conventional learning methods. The study population consisted of randomly selected class X pupils from SMA Negeri 2 Tondano, who were divided into control and experimental groups. The experimental class consisted of 25 students who received instruction using the project-based learning model, while the control class consisted of 22 students who received instruction using the conventional paradigm. Data collection was conducted by administering a pre-test prior to administering the treatment, followed by a post-test after the treatment was provided. The research yielded an average post-test score of 0.0842 for the experimental class and 0.075 for the control class. Statistical tests, specifically the t-test, were conducted to compare the learning results of the experimental class and the control class. The calculated tcount 17.164176, was found to be more than the critical ttable 1.67943. Therefore, the null hypothesis (H0) is rejected. The null hypothesis H0 is rejected at a significance level of 0.05. Therefore, it may be inferred that the project-based learning paradigm has an impact on students' learning results in the subject of growth substance.